Eczema and atopy in early childhood: low IgA plasma cell counts in the jejunal mucosa. Issue 12 (December 1981) - Sloper, K S; Brook, C G; Kingston, D; Pearson, J R; Shiner, M
Abstract : Twenty-one children aged between 2 and 54 months, 14 with eczema and 7 with allergies in first-degree relatives, were referred for diagnostic jejunal mucosal biopsy for a variety of symptoms. A partial villous atrophy was found in 19 of the 21 biopsies obtained; the other 2 were normal. We report a highly significant (P less than 0.0001) lower IgA cell count in biopsies with partial villous atrophy compared with the results of our previous study of IgA and IgM plasma cells in the mucosal biopsies in children without eczema or a history of atopy matched for age and histological appearances. The IgM cell count was also lower.